Secreted aspartate proteinases, a virulence factor of Candida spp.: occurrence among clinical isolates - Hamal, P; Dostál, J; Raclavský, V; Krylová, M; Pichová, I; Hrusková-Heidlngsfeldová, O (Folia microbiologica, 2004)
Production of secreted aspartate proteinases was determined in a set of 646 isolates of Candida and non-Candida yeast species collected from 465 patients of the University Hospital in Olomouc (Czechia) in the period 1995-2002, and Candida samples obtained from 64 healthy volunteers using solid media developed for this purpose. Using random amplified polymorphic DNA analysis (RAPD) 79 Candida isolates from blood were analyzed to show potential relationships between clustering of the fingerprints and extracellular proteolytic activity of these strains. C. albicans, C. tropicalis and C. parapsilosis possess always proteolytic activity while non-Candida species did not display any proteolysis. A tight relationship between fingerprints and extracellular proteolysis in the Candida isolates was not shown. A remarkable consistency between fingerprint clusters and proteolysis occurred in a subset of C. parapsilosis samples. Suboptimal pH of the growth medium was shown to facilitate the investigation of potential co-incidence of genotypic and phenotypic traits.
Keywords: mužské pohlaví; aspartátové endopeptidasy; ženské pohlaví; Fungal Proteins; Virulence Factors; technika náhodné amplifikace polymorfní DNA; Humans; faktory virulence; lidé; Aspartic Acid Endopeptidases; fungální proteiny; Female; Hydrogen-Ion Concentration; Random Amplified Polymorphic DNA Technique; Candida; Male; koncentrace vodíkových iontů